2020
DOI: 10.3390/ijms21114019
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Electrospun Sustainable Composites for Biomedical, Environmental, Energy, and Packaging Applications

Abstract: Electrospinning has gained constant enthusiasm and wide interest as a novel sustainable material processing technique due to its ease of operation and wide adaptability for fabricating eco-friendly fibers on a nanoscale. In addition, the device working parameters, spinning solution properties, and the environmental factors can have a significant effect on the fibers’ morphology during electrospinning. This review summarizes the newly developed principles and influence factors for electrospinning technology in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 155 publications
(228 reference statements)
0
36
0
Order By: Relevance
“…In order to overcome this, several samples of zein-citrate solutions were prepared and spun in sequential order on a day with low humidity; ideally, the humidity should be below 20% to allow the solvent to evaporate off during the spinning process. Note, however, that electrospinning is also hindered by high humidity [55]. Solutions could not be prepared in advance, as this would cause solutions to become too viscous to air-spray.…”
Section: Reflection and Future Considerationsmentioning
confidence: 99%
“…In order to overcome this, several samples of zein-citrate solutions were prepared and spun in sequential order on a day with low humidity; ideally, the humidity should be below 20% to allow the solvent to evaporate off during the spinning process. Note, however, that electrospinning is also hindered by high humidity [55]. Solutions could not be prepared in advance, as this would cause solutions to become too viscous to air-spray.…”
Section: Reflection and Future Considerationsmentioning
confidence: 99%
“…Electrospinning allows exceptional versatility to produce fiber scaffolds with targeted properties [ 1 ]. Varying some electrospinning parameters, features of the morphology can be enhanced, resulting in better mechanical properties [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The electrospun nanofibers’ properties such as morphology and diameter are influenced by intrinsic (solution properties) and extrinsic (process and environment) factors [ 202 , 203 , 204 ]. Dorati et al [ 205 ] reported that solvent concentration, viscosity, electrical conductivity, and elasticity are the most influential parameters on the geometry and morphology of electrospun nanofibers.…”
Section: Current Progress On Elaboration Process Implementation mentioning
confidence: 99%